Protection of the Arctic Marine Environment (PAME) Working Group 2-pager Summary Progress report - Protection of the Arctic Marine Environment (PAME) (Arctic Council Secretariat, 2016)
Protection of the Arctic Marine Environment Working Group's progress report to SAOs, including list of anticipated deliverables to the 2017 Fairbanks Ministerial meeting.